Pengaruh Terapi Psikoedukasi Keluarga terhadap Tingkat Kemandirian Orang dengan Gangguan Jiwa - Karame, Verra; Lontoh, Esther; Tampodung, Valeri (JURNAL ILMIAH KESEHATAN MANADO, 2025)
People with schizophrenia will experience interference in their independence in carrying out functions and roles in daily life, such as caring for themselves, going to school or work and other functions. The factor that causes the high recurrence rate of schizophrenia is that families do not know how to handle clients with mental disorders when they return to the family environment, making it a burden for the family. Family psychoeducation is a form of family mental health care therapy by providing information and education through therapeutic communication. The aim of the research is to determine the effect of family psychoeducation therapy on the level of independence of people with mental disorders at the Prof. Mental Hospital. Dr. Vl. Ratuumbuysang, Manado City. This research is a quasi-experimental research. The research was carried out in May 2025 at the Prof. The conclusion from the research results is that there is an influence of family psychoeducation therapy on the level of independence of people with mental disorders at the Prof. Mental Hospital. Dr. Vl. Ratumbuysang Manado City.